Staying Put: The Endeavors and Wisdoms of Farmers in Twenty-first-century Sustainable Agriculture. (August 2014) - Christensen, Angela
Throughout the twentieth century, food production in America drastically changed in conjunction with social and historical events. The ramifications of America's agricultural endeavors are evident in polluted waterways, soils, and air, along with myriad health problems like diabetes and obesity linked to highly processed foods. Over the last three decades, sustainable agriculture, seen in the form of farmers' markets, organic food, and local food, has swept across America. The desire by an ever-growing population to see food production become more localized and tangible is witnessed in the increasing amount of literature dedicated to the topic of sustainable agriculture. Although critiqued by some as a step backward in the progress of agriculture, sustainable agriculture continues to gain momentum (Beus and Dunlap 1990; Gardner 2002; Vogeler 1981). Drawing on literature, documents, and semi-structured interviews with sustainable farmers in the Western United States, I explore why farmers choose to farm in a sustainable manner and how their philosophies of sustainable farming drive their everyday practices.